Performance and applications of lightweight foamed concrete with various density - Law, Chin Yong, 1991-, author 594806; Shek, Poi Ngian, supervisor 182086; Fakulti Kejuruteraan. Sekolah Kejuruteraan Awam 619085 (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2017)
Thesis (Sarjana Kejuruteraan (Awam - Struktur))